Security constrained unit commitment with multiple wind farms integrated - Rong Ye; Haoyong Chen; Pan Chen (2010 Conference Proceedings IPEC, 2010)
Wind power generation brings new challenges to Security-Constrained Unit Commitment and Security-Constrained Economic Dispatch due to the uncertainty caused by its imprecise prediction. Especially when multiple wind farms are taken into consideration, mixed integer programming method which is good at dealing with deterministic SCUC problems doesn't work. This paper introduces generalized generation distribution factors and replaces the method based on monte carlo simulation with the one based on extreme scenarios set, in order to improve the method from the aspect of its computing time and precision. The modified IEEE118 bus system proves that the proposed method can acquire a unit commitment plan more quickly for better wind power uncertainty adaptability.